Cometh The Hour - Archer, Jeffrey; Jennings, Alex; Macmillan Audio (Firm) (New York : Macmillan Audio, 2016)
Giles Barrington must decide if he should withdraw from politics and try to rescue Karin. Lady Virginia can see no way out of her financial problems, until she is introduced to the hapless Cyrus T. Grant III. Sebastian Clifton is now the Chief Executive of Farthings Bank, whose personal life is thrown into disarray when he falls for Nadira, a beautiful Indian girl. Harry Clifton remains determined to get Anatoly Babakov released from a gulag in Siberia. Harry's wife Emma convinces her new friend Margaret Thatcher to raise the subject with the Russian President. But then something unexpected happens that none of them could have anticipated. This is the penultimate book in the Clifton Chronicles.
Keywords: Families -- Fiction -- History -- 20th century -- England; Social classes -- Fiction -- England; Audiobooks; Domestic fiction; Historical fiction; Audiobooks